Strategi Strategi Pemasaran Jiandy Wedding Organizer Dalam meningkatkan Kualitas Layanan Jasa di Desa Leppangeng Kecamatan Patampanua Kabupaten Pinrang - bila, nabilah_bila; Adam Latif; Rahman Yakub; Haslindah (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
This research is motivated by the significance of marketing strategies in enhancing service quality, particularly in service-based businesses such as Jiandy Wedding Organizer in Leppangeng Village. The purpose of this study is to identify the marketing strategies implemented by Jiandy Wedding Organizer to improve customer service quality. A descriptive qualitative method was employed, with data collected through observation, interviews, and documentation. The data were analyzed using the Nvivo 12 application to systematically group themes and organize categories based on the interview results. The findings reveal that Jiandy Wedding Organizer effectively applies the 4P marketing mix (product, price, place, promotion), including offering a variety of wedding packages, competitive pricing, promotion through social media, and fast, friendly service. In conclusion, the implemented marketing strategies have successfully increased customer satisfaction and strengthened the business image amid competition from similar service providers.